Ռումի սուլթանության հակաթոռ կաթողիկոս Անանիան - Մաթևոսյան, Կարեն (Մատենադարան)
The information given in the history of Kirakos Gandzakets‘i, in the Chronicles of the Anonymous of Edessa and Step‘anos Orbelean, in four colophons of Armenian manuscripts and in other sources witness that in 1201–1227, in the Sultanate of Rum, in Kayseri, and after some time in Sebastia (Sivas), there was a catholicosate (patriarchate) under the leadership of Anania, nicknamed Khayt. He probably descended from the family of the 11th century Catholicos Petros Getadardz and claimed to be the Catholicos of all Armenians. Not having achieved his goal in Cilicia, in 1201 he created a catholicosate on the territory of the Sultanate of Rum by the consent of Sultan Rukn ad-Din Suleimanshah II. Anania enjoyed the favor of the local authorities, since the existence of this catholicosate separated in spiritual and ecclesiastical terms the Armenians living in the territory of the sultanate from the Catholicosate of All Armenians located in Hromkla and from the Armenian Kingdom of Cilicia. The article clarifies some facts of Anania's life and work. It is demonstrated that the Catholicos of All Armenians Yovhannēs Ssets‘i (1203–1221), King Levon I (1198–1219), and later also Catholicos Constantine (1221-1267) tried to achieve the obedience of the anti-Catholicos, but without result, and that in 1227 with the death of Anania the catholicosate founded by him in the Sultanate of Rum ceased to exist. A study of the text of the Martyrdom of Theodore Kesarats‘i revealed that it was written in 1204 in Kayseri, at the behest of Anania. Among other issues, the question of the date of Anania’s death in the inscription on his tombstone is also discussed in the article. Сведения, сохранившиеся в истории Киракоса Гандзакеци, в летописях Анонима Эдесского и Степаноса Орбеляна, в четырех памятных записях армянских рукописей и в других источниках показывают, что в 1201-1227 гг. в Румском (Иконийском) султанате, в Кесарии (Кайсери), а через некоторое время в Себастии (Сивас), существовал католикосат (патриарший престол) под предводительством Анании по прозвищу Хайт. Он вероятно происходил из рода католикоса XI века Петроса Гетадарца и претендовал на место католикоса всех армян, но не достигнув своей цели в Киликии, в 1201 г. создал католикосат на территории Румского султаната с согласия султана Рукн ад-Дина Сулейманшаха II. Анания пользовался благосклонностью местных властей, так как существование этого католикосата в духовном и церковном отношении отделяло армян, живущих на территории султаната, от находящегося в Ромкле католикосата всех армян и от Киликийского Армянского царства. В статье уточнены некоторые факты жизни и деятельности Анании. Показано, что католикос всех армян Ованес Ссеци (1203-1221) и царь Левон I (1198-1219), а в последствии также католикос Константин (1221-1267) пытались добиться покорности антикатоликоса, но результатов не добились, и что 1227 г. со смертью Анании основанный им католикосат в Румском султанате перестал существовать. На основании изучения текста “мученичества Феодора Кесарийского” предполагается, что оно было написано в 1204 г. в Кесарии, по велению Анании. Рассматривается вопрос о дате смерти Анании в надписи на его надгробном камне, и т. д.
Keywords: Պատմություն